(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
(Purpose)This review article is designed to expose physiotherapist to a assessment andmanagement of stress urinary incontinence treatment of SUI along with preventive roles thatphysiotherapy at for women with urinary incontinence. Unique concept about this article is to providebasic functions of pelvic floor muscles and support for the continence of urine.(Method) A range ofdatabase was searched to identified article that addresses physiotherapy for SUI including Cochranelibrary ,MedlineCINAHI.(Result)According to this article identified in our database greater evidentresults have been observed in females with SUI who receives treatment for at least 3months.(Conclusion)Plan of physiotherapy should be varied from person to person and include vitalsupervision.